Coastal Community Welfare Improvement through Optimization of Integrated Pond Farming Management in Indonesia - Alimudin Laapo; Dafina Howara (International Journal of Agriculture System, 2016)
The lack of tenure and limited production factors causing coastal communities always be trapped on the circle of poverty, or far from prosperous. The research objective is to optimize the use of seaweed production factors that integrated with milkfish to improve the welfare of coastal communities in Indonesia. Data analysis employed Multiple Goal Programming methods. The results showed that the average of pond tenure by farmers covering 5,1 Ha with seaweed production 13,191 tons, and profits IDR76,347,700.0 per year (1USD equal to 13,000IDR). The maintenance costs of pond is the kind of production factor that limited availability, while production factors seeds, seedlings, fertilizers, and pesticides, are relatively available to farmers. Optimization results the integrated management of pond show the maximum revenue is achieved IDR1,089.89 million, labor employment 72 people, and target of seaweed production reached 188.65 tons. This means that the welfare of the farmers can be improved through the expansion of pond, and the addition of the production factor, especially capital and fertilizer.